PELAKSANAAN PROGRAM UNGGULAN TAHFIDZ AL-QUR’AN DALAM PENANAMAN KARAKTER DISIPLIN DAN ADVERSITY QUOTIENT SISWA KELAS VII MADRASAH TSANAWIYAH NEGERI 1 KUDUS - Nurul Faizatur Rohmah; Mukh. Nursikhin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
Today's national education is facing several major crises, one of which is the decline in student discipline. To respond to this, educational institutions have made innovations by offering character-building support programs, such as the tahdiz al-Qur'an program. The aim is to find out the design of the flagship program, to know the implementation of the flagship tahfidz al-Qur'an program and to find out the evaluation of the flagship program for tahfidz al-Qur'an in instilling the character of discipline and student adversity quotient. The research method uses descriptive qualitative type. For data collection techniques through observation, interviews, and documentation. The results showed: 1) the superior program of tahfidz al-Qur'an in cultivating disciplinary character was carried out through tahfidz activities both in class and at boarding schools with coaching, habituation, supervision, and assignment methods. As for the planting of adversity intelligence on tahfidz students can be identified through tahsin, memorization, murajaah, semaan activities, and the presence of memorization targets, 2) evaluation of the superior tahfidz al-Qur'an program in cultivating disciplinary character and AQ including evaluation of context, input, and results. The implication of this research is that the cultivation of the character of discipline in determining the success of learning is something that is important and needs to be improved, so that with discipline, learning targets and planning can be controlled and in accordance with the target time pursued.